PENERAPAN METODE FIELD TRIP UNTUK MENINGKATKAN HASIL BELAJAR MATERI BAGIAN-BAGIAN TUMBUHAN PADA SISWA KELAS IV SD NEGERI 134417 PEMATANG SIANTAR TAHUN PELAJARAN 2017/2018 - SUMARNY TRIDELPINA PURBA PURBA (JURNAL ILMIAH SIMANTEK, 2019)
This study aims to describe the increase in student learning outcomes and activities in the material of plant parts by applying field trip learning methods in class IV 134417 Public Elementary School Pematang Siantar 2017/2018 school year. This research is a classroom action research carried out in two cycles with two meetings each cycle. The research subjects were grade IV students of 134417 Public Elementary School Pematang Siantar 2017/2018 school year, totaling 32 students. Learning outcomes data were obtained through tests while learning activity data was obtained through observation sheets of student learning activities. The results of the study show that; 1) field trip learning methods can improve student learning outcomes, as evidenced by the results of the students' classical completeness test up from Cycle I by 59% to 88% in Cycle II, so that they successfully provide completeness of classical learning outcomes and achieve established research success criteria; 2) field trip learning methods can improve student learning activities, as evidenced by observers observations in Cycle I writing and reading activities 38%, working on LKS 36%, asking fellow friends 8%, asking teachers 14%, and which is not relevant to KBM 4 %. Whereas in Cycle II the activity of writing and reading 33%, applying 40% LKS, asking fellow friends 18%, asking the teacher 6%, and which is not relevant to KBM 3%.